2020
DOI: 10.1021/acsomega.0c00388
|View full text |Cite
|
Sign up to set email alerts
|

Edge Defect-Free Anisotropic Two-Dimensional Sheets with Nearly Direct Band Gaps from a True One-Dimensional Van der Waals Nb2Se9 Material

Abstract: Dangling-bond-free two-dimensional (2D) materials can be isolated from the bulk structures of one-dimensional (1D) van der Waals materials to produce edge-defect-free 2D materials. Conventional 2D materials have dangling bonds on their edges, which act as scattering centers that deteriorate the transport properties of carriers. Highly anisotropic 2D sheets, made of 1D van der Waals Nb2Se9 material, have three planar structures depending on the cutting direction of the bulk Nb2Se9 crystal. To investigate the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…Recently a particular class of semiconductor nanostructures has emerged1D nanowires of 2D van der Waals crystals, which combine the distinct structure of layered materials, i.e., covalent bonding within the layers and weak van der Waals bonding between them, and 1D confinement achieved in nanowires. This is distinct from efforts of separating quasi-1D nanostructures by exfoliation from bulk materials made possible by the presence of anisotropy in the crystal structure of transition-metal trichalcogenides such as TiS 3 , , TaSe 3 , , ZrSe 3 , NbS 3 , Sb 2 Se 3 , , Ta 2 Pd 3 Se 8 , as well as 1D nanostructures in which the van der Waals units represent true 1D chains (V 2 Se 9 , Nb 2 Se 9 , etc.). It is well established that nanowires of conventional 3D semiconductors grow with a preferred crystal orientation, e.g., with the symmetry axis along the [111] direction for Si and Ge nanowires .…”
Section: Introductionmentioning
confidence: 98%
“…Recently a particular class of semiconductor nanostructures has emerged1D nanowires of 2D van der Waals crystals, which combine the distinct structure of layered materials, i.e., covalent bonding within the layers and weak van der Waals bonding between them, and 1D confinement achieved in nanowires. This is distinct from efforts of separating quasi-1D nanostructures by exfoliation from bulk materials made possible by the presence of anisotropy in the crystal structure of transition-metal trichalcogenides such as TiS 3 , , TaSe 3 , , ZrSe 3 , NbS 3 , Sb 2 Se 3 , , Ta 2 Pd 3 Se 8 , as well as 1D nanostructures in which the van der Waals units represent true 1D chains (V 2 Se 9 , Nb 2 Se 9 , etc.). It is well established that nanowires of conventional 3D semiconductors grow with a preferred crystal orientation, e.g., with the symmetry axis along the [111] direction for Si and Ge nanowires .…”
Section: Introductionmentioning
confidence: 98%
“…[20,21] Besides TMTCs, other 1D-vdW materials such as Te, Nb 2 Se 9 , and Sb 2 X 3 (X = S or Se) have the structural advantage of dangling bond-free on their edges as well as surfaces, which act as charge carrier scattering sites that deteriorate the transport property. [22][23][24][25] In addition, it was theoretically proved that some of the 1D-vdW materials exhibit thickness-dependent bandgap properties with indirectto-direct transition. [26][27][28] Based on these aspects, 1D nanowire materials are expected to promote development in the electronic application, but there are still many things to be explored in terms of material diversity.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Especially, 1D vdW materials possessing strong covalent intrachain bonds and weak interchain vdW interactions have the structural advantage of dangling bonds-free on their edges, which act as charge carrier scattering sites that deteriorate the transport property. [18][19][20][21] Moreover, it was theoretically confirmed that some of the 1D vdW materials exhibit thickness-dependent properties, such as the bandgap expansion with the indirect-to-direct transition as the number of unit chains decrease from their bulk crystal, similar to well-studied transition metal dichalcogenides (TMDs). [22][23][24][25] Based on this aspect, numerous studies have been conducted to utilize 1D nanowires in functional electronic devices such as FET [26][27][28][29] and photodetectors, [30][31][32][33] but diversity among promising materials is still limited.…”
Section: Introductionmentioning
confidence: 99%